LigaSure versus conventional dissection technique in pancreatoduodenectomy: a pilot study - Gehrig, Tobias; Müller, Beat P.; Kenngott, Hannes Götz; Fischer, Lars; Mehrabi, Arianeb; Büchler, Markus W.; Gutt, Carsten N. (The American journal of surgery, 2011)
Background - Pancreatic surgery requires extensive preparation and tissue dissection. Therefore, LigaSure (Valleylab, Boulder, CO) provides an alternative to conventional dissection techniques. The aim of the present study was to describe the feasibility, safety, and cost efficiency of LigaSure in pancreatoduodenectomy. - Methods - Seven patients underwent surgery with the Ligasure and 7 patients underwent surgery with conventional dissection techniques. The patients were investigated for surgical time, intraoperative blood loss, complications, mortality, duration of hospital stay, and surgery-related costs. - Results - Surgical time was 207 minutes in the LigaSure group and 255 minutes in the conventional group (P = .020). Intraoperative blood loss was 271 and 771 mL, respectively (P = .010). Other perioperative outcomes were comparable. The respective surgery-related costs averaged €4,125 and €4,931 (P = .023). - Conclusions - The use of LigaSure in pancreatoduodenectomy seems to be feasible and safe. In addition, it might lead to a reduction in the surgery-related costs.
Gesehen am 10.10.2023
Online verfügbar ab 23. September 2010